2015
DOI: 10.1007/s00264-015-2880-x
|View full text |Cite
|
Sign up to set email alerts
|

The use of navigation in medial opening wedge high tibial osteotomy can improve tibial slope maintenance and reduce radiation exposure

Abstract: Level III, retrospective comparative study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…The target correction angle in coronal alignment was presented with different radiographic parameters in each study: hip–knee–ankle angle (HKA) in seven studies 14 , 15 , 17 , 18 , 20 , 24 , 31) , femorotibial angle (FTA) in two studies, which were reports of the same authors 12 , 13) , and weight bearing line coordinate (WBL) in seven studies ( Table 2 ) 11 , 13 , 14 , 16 , 18 , 19 , 31) . The target was similar but not perfectly identical across the studies.…”
Section: Resultsmentioning
confidence: 99%
“…The target correction angle in coronal alignment was presented with different radiographic parameters in each study: hip–knee–ankle angle (HKA) in seven studies 14 , 15 , 17 , 18 , 20 , 24 , 31) , femorotibial angle (FTA) in two studies, which were reports of the same authors 12 , 13) , and weight bearing line coordinate (WBL) in seven studies ( Table 2 ) 11 , 13 , 14 , 16 , 18 , 19 , 31) . The target was similar but not perfectly identical across the studies.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that postoperative PTS increases in patients who underwent OWHTO with navigation is significantly lower than that in the conventional group, but postoperative coronal alignment in both groups were almost identical. [23][24][25][26] Increased PTS in knees with intact anterior cruciate ligaments might cause more anterior cruciate ligament tension because increased PTS in knees with deficient anterior cruciate ligaments after OWHTO redistribute tibiofemoral contact pressures posteriorly. 12 Maintaining original PTS is crucial, but very few surgeons use a computer navigation system during OWHTO.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is unclear whether preoperative 3D planning contributes to more precise postoperative realignment in the clinical setting. We hypothesize that clarifying both issues in OWHTO will provide clinically relevant information for intraoperative decision‐making in the absence of a computer‐assisted navigation system that surgeons have used to control PTS …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Computer-assisted HTO can also provide real-time intraoperative information concerning coronal, sagittal and transverse axes, which can compensate for the shortcomings of preoperative radiographic planning. It can improve postoperative results with decreased radiation exposure 731)…”
Section: Advantages and Literature Reviewmentioning
confidence: 99%